Deep wound cultures correlate well with bone biopsy culture in diabetic foot osteomyelitis. Issue 7 (20th September 2013) - Malone, M.; Bowling, F. L.; Gannass, A.; Jude, E. B.; Boulton, A. J. M.
Abstract Background Osteomyelitis is a major complication in patients with diabetic foot ulceration. Accurate pathogenic identification of organisms can aid the clinician to a specific antibiotic therapy thereby preventing the need for amputation. Methods All diabetic patients with bone biopsy‐confirmed osteomyelitis were included into the study: biopsies were performed either during surgical removal of infected bone or percutaneously under guided fluoroscopy through non‐infected tissue. The depth and extent of the ulcer was assessed using a sterile blunt metal probe. Deep wound cultures were taken from the wound base after sharp debridement. Results Of 66 cases of suspected osteomyelitis in 102 joints, 34 patients had both bone biopsies and deep wound cultures over the study period. Thirty two of 34 (94%), had a history of preceding foot ulceration, and in 25 of the cases a positive probe to bone test was recorded. In a high proportion of patients, at least one similar organism was isolated from both the deep wound culture and bone biopsy procedures (25 of 34 cases, 73.5%, p<0.001). When organisms were isolated from both wound cultures and bone biopsies, the identical strain was identified in both procedures in a significant proportion of cases (16 of 25 cases, 64%, p<0.001, total sample analysis in 16 of 34 cases, 47%). Conclusions Deep wound cultures correlate well with osseous cultures and provide a sensitive method in assessing and targeting likely pathogens that cause osseous infections. This will help aid the clinician in guiding antibiotic therapy in centers where bone biopsies may not be readily available. Copyright © 2013 John Wiley & Sons, Ltd.